2020
DOI: 10.3390/cells9041007
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Reinnervation of Denervated Areas Following Nerve Injury Facilitates Neuropathic Pain

Abstract: An injury to peripheral nerves leads to skin denervation, which often is followed by increased pain sensitivity of the denervated areas and the development of neuropathic pain. Changes in innervation patterns during the reinnervation process of the denervated skin could contribute to the development of neuropathic pain. Here, we examined the changes in the innervation pattern during reinnervation and correlated them with the symptoms of neuropathic pain. Using a multispectral labeling technique—PainBow, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…It was recently demonstrated that neuropathic pain following nerve injury was associated with a decreased number of DRG neuronal somata innervating the hypersensitive area (Leibovich et al, 2020) and increased number of axons innervating the area (Duraku et al, 2012). Together these results suggest that each DRG neuron innervating the hypersensitive area increases the complexity of its terminal fibers.…”
Section: Discussion (1355 Words)mentioning
confidence: 85%
“…It was recently demonstrated that neuropathic pain following nerve injury was associated with a decreased number of DRG neuronal somata innervating the hypersensitive area (Leibovich et al, 2020) and increased number of axons innervating the area (Duraku et al, 2012). Together these results suggest that each DRG neuron innervating the hypersensitive area increases the complexity of its terminal fibers.…”
Section: Discussion (1355 Words)mentioning
confidence: 85%
“…An increase in the number of terminal branches to 16, simulating hyperinnervation changes (Cain et al, 2001;Leibovich et al, 2020) leads to an increase in firing (Figure 12A, red). A decrease in the number of the terminal branches to 7, simulating a denervation state, substantially decreases the nociceptive gain (Figure 12A, blue).…”
Section: Resultsmentioning
confidence: 99%
“…Together these results suggest that each DRG neuron innervating the hypersensitive area increases the complexity of its terminal fibers. Our model predicts that the increase in the terminal branching of individual DRG neurons following nerve injury (Leibovich et al, 2020) or inflammation or tumor formation (Cain et al, 2001) affects neuronal excitability and thus may contribute to the development of pain hypersensitivity in neuropathic conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a further approach, they enhanced the sprouting of nerves by the drug oubain and observed that this treatment drastically reduced the neuropathic pain behavior. From these results, it can be concluded that dysfunctional reinnervation of injured areas is involved in the development of neuropathic pain and that pharmacological support of reinnervation, e.g., by oubain, might exert a useful approach for the treatment of nerve injury-induced pain [ 13 ]. David Romeo-Guitart and Caty Casas described a new approach to modulate axonal regeneration and neuropathic pain at the same time by the use of a drug combination called NeuroHeal which has been identified using machine learning [ 14 ].…”
mentioning
confidence: 99%